3.1k views
6 votes
I NEED ASAP HELP 100 POINTS+BRAINLEYIST

I NEED ASAP HELP 100 POINTS+BRAINLEYIST-example-1

2 Answers

5 votes


\\ \rm\Rrightarrow (x+3)/(3)=(y+2)/(2)


\\ \rm\Rrightarrow (x)/(3)+1=(y+2)/(2)


\\ \rm\Rrightarrow (x)/(3)=(y+2)/(2)-1


\\ \rm\Rrightarrow (x)/(3)=(y+2-2)/(2)


\\ \rm\Rrightarrow (x)/(3)=(y)/(2)

User Dbkk
by
5.2k points
0 votes

Answer:


(x)/(3)=(y)/(2)

Explanation:


\begin{aligned}(x+3)/(3) & = (y+2)/(2)\\\\\implies (x)/(3)+(3)/(3) & = (y)/(2)+(2)/(2)\\\\(x)/(3)+1 & = (y)/(2)+1\\\\(x)/(3)+1-1 & = (y)/(2)+1-1\\\\(x)/(3) & = (y)/(2)\end{aligned}

User Pranav Kapoor
by
5.3k points